High-Altitude Maculopathy in Mountaineers: A Systematic Review and Meta-Analysis - Rataya Paramitha Maliawan; I Made Ady Wirawan; I Gusti Ayu Made Juliari; Ida Ayu Ary Pramita (HM Publisher, 2026)
Background: High-altitude maculopathy (HAM) represents a distinct form of high-altitude retinopathy affecting mountaineers at extreme elevations. Despite increased mountaineering activity, the prevalence and clinical significance of HAM remain poorly characterised in systematic reviews. Methods: A comprehensive systematic review and meta-analysis were conducted following PRISMA 2020 guidelines. Databases searched included PubMed, Scopus, Cochrane Library, and manual review of reference lists through April 2026. Eligible studies were prospective and retrospective cohorts reporting HAM prevalence in mountaineers at altitude ≥3,500 metres. Risk of bias was assessed using the Newcastle-Ottawa Scale. Meta-analysis employed the Freeman-Tukey double arcsine transformation with DerSimonian-Laird random-effects modelling. Results: Three prospective studies (n=50 mountaineers) were analysed with a pooled prevalence of 73.37% (95% confidence interval: 60.28–84.72%). Heterogeneity was absent (I²=0%, Q=0.78, p=0.678). Subgroup analysis demonstrated a higher prevalence at extreme altitude (≥5,000 m: 78.6%) versus very high altitude (3,500–4,999 m: 70%). Sensitivity ranged 67.48–83.76%. Funnel plot inspection revealed no evidence of publication bias. Conclusion: Approximately three-quarters of mountaineers experience HAM at high altitude, with prevalence increasing at extreme elevations. HAM represents a common but underrecognised altitude-related ocular complication. Future prospective studies should employ standardised diagnostic criteria and investigate the mechanistic pathways of macular involvement.